CHF6523 data suggest that the phosphoinositide 3-kinase delta isoform is not a suitable target for the management of COPD - Govoni, Mirco; Bassi, Michele; Girardello, Luca; Lucci, Germano; Rony, François; Charretier, Rémi; Galkin, Dmitry; Faietti, Maria Laura; Pioselli, Barbara; Modafferi, Gloria; Benfeitas, Rui; Bonatti, Martina; et al. (Respiratory research, 2024)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory condition. Given patients with COPD continue to experience exacerbations despite the availability of effective therapies, anti-inflammatory treatments targeting novel pathways are needed. Kinases, notably the phosphoinositide 3-kinases (PI3K), are thought to be involved in chronic airway inflammation, with this pathway proposed as a critical regulator of inflammation and oxidative stress response in COPD. CHF6523 is an inhaled PI3Kδ inhibitor that has shown positive preclinical results. This manuscript reports the results of a study of CHF6523 in patients with stable COPD (chronic bronchitis phenotype), and who had evidence of type-2 inflammation.